2014
DOI: 10.1007/s00280-014-2622-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative neutrophil-to-lymphocyte ratio predicts response to first-line platinum-based chemotherapy and prognosis in serous ovarian cancer

Abstract: Our findings indicated that high levels of preoperative NLR might be a potential biomarker of worse response to first-line platinum-based chemotherapy and poor clinical outcomes in patients with SOC. Further validation of this easily available parameter as a potential stratification tool in prospective studies should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…One explanation is that NLR and PLR may also increase secondarily as systemic inflammation increases [7]. These factors are expected to detect advanced-stage disease and thereby predict prognosis similar to serum CA-125 levels in early-stage EOC [1333]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation is that NLR and PLR may also increase secondarily as systemic inflammation increases [7]. These factors are expected to detect advanced-stage disease and thereby predict prognosis similar to serum CA-125 levels in early-stage EOC [1333]. …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, clinical biomarkers using systemic inflammation and coagulation has been suggested to be useful to predict prognosis of EOC with the advantage of being clinically easily measured [9]. In particular, systemic inflammation leading to secondary hematological changes has been shown in various types of malignancies [1011], and changes, such as the neutrophil to lymphocyte ratio (NLR) and the platelet to lymphocyte ratio (PLR), have been investigated as prognostic biomarkers in EOC [1213]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, PLRs have been used as an independent predictor of survival in patients with ovarian cancer [13]. In addition, the use of NLR could not only apply as a prognostic marker, but also aid in treatment choices in ovarian cancer [12,14,16,17]. Furthermore, variation in the reported NLR threshold used to assign patients to high-risk or low-risk cohorts complicates the application of a single NLR determination for patient’s prognostic prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Risk of malignancy index (RMI) which includes ca125, ultrasound findings and menopausal status have been developed for this purpose. The increasing evidences emphasize the importance of inflammation in the initiation, promotion, invasion and metastasis of cancer [5]. It was found that neutrophils increased and lymphocytes relatively decreased as a result of the systemic inflammatory response [8].…”
Section: Discussionmentioning
confidence: 99%
“…As preoperative inflammatory markers, neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been suggested to be useful for discriminating malignant and benign ovarian tumors. NLR and PLR are noninvasive, easily measured, universally known and cost-effective markers [57]. …”
Section: Introductionmentioning
confidence: 99%